2000
DOI: 10.1016/s0029-7844(00)01075-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric risks of pregnancy in women less than 18 years old

Abstract: Pregnant women less than 18 years old were more likely to deliver preterm than older women. In most other respects they have less maternal and perinatal morbidity and were more likely to have normal vaginal deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
124
2
21

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 20 publications
18
124
2
21
Order By: Relevance
“…Young mothers had a higher rate of anemia with the antenatal hemoglobin concentration <10 g/dL which corresponded to previous study [14,18]. This might be the result of poor nutrition during pregnancy [18].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Young mothers had a higher rate of anemia with the antenatal hemoglobin concentration <10 g/dL which corresponded to previous study [14,18]. This might be the result of poor nutrition during pregnancy [18].…”
Section: Discussionsupporting
confidence: 88%
“…About 4.2% of extremely young maternal age (≤ 16 years) had no prenatal care which might be the reason for unintended pregnancy, poverty, ignorance of pregnancy signs and symptoms and lack of knowledge of antenatal care [14,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some pathophysiological mechanisms have been proposed -the pelvic bones and the birth canal were suggested to be in the process of growth, which may lead to the increased risk of prolonged and obstructed labor, episiotomy, use of forceps and/or ventouse, and puerperal endometritis [10]. According to this theory, it is generally expected to see higher cesarean section rates in these women as seen in previous studies [10][11][12]; however, consistent with the previous studies [6,13,14], our data revealed a 17% cesarean section rate in the early-middle adolescent group that was significantly lower as compared to the other groups. Although the study observed a higher rate of PD in early-middle adolescent groups, LBW incidence was similar among groups.…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of socioeconomic factors have been proposed for the increased risk of poor pregnancy outcome in early age group -including inadequate prenatal care, poverty, unmarried status, low educational levels, psychological stress, and illicit drug use [12,6]. Some studies indicated the age to be the main determinant for the increased risk, independent from the previously discussed socioeconomic factors [10,11,17,18]. It was speculated that the growing body requirements of an adolescent mother may lead to competition between the mother and fetus [2,17].…”
Section: Discussionmentioning
confidence: 99%